Strategy for Increasing Farmers' Welfare through Capacity Building for Organic Fertilizer Production Technology in Japeledok Village, Rembang Regency - Hery Sulistio Jati; Tetuko Rawidyo Putro*; Lukman Hakim; Mulyanto Mulyanto; Siti Aisyah Tri Rahayu; Riwi Sumantyo; Johadi Johadi; ARIYANTO ADHI NUGROHO; Muhammad Bagus Sistriatmaja; Andri Prasetyo (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Farmers of food crops, especially rice commodities in Rembang Regency, face the main challenge, namely the increase in the cost of agricultural production. Even though the productivity of rice commodities has increased, the high production costs have affected the income levels of farmers and have had an impact on the welfare of farmers. The stagnation of Farmers' Terms of Trade (NTP) for food crops from 2014-2019 amid an increase in the productivity of food crop agriculture shows that agricultural production costs are the main obstacle to increasing farmer welfare. Efforts to reduce agricultural production costs are a factor in encouraging the welfare of farmers in Rembang Regency. The self-sufficiency of organic fertilizers is one of the cost-efficiency solutions for producing agrarian food crops. Increasing the independence capacity of farmers' fertilizers, especially organic fertilizers, is a strategy to reduce agricultural production costs. There are at least four steps taken to increase farmer capacity: 1) preparation of a theoretical framework for change; 2) counseling on the benefits of organic fertilizers; 3) organic fertilizer production training, and 4) evaluation. The results of this capacity building show an increase in farmers' knowledge and skills in producing organic fertilizer in Japeledok Village, Rembang Regency. Farmers then use knowledge and skills to increase the cost efficiency of fertilizer production to improve the welfare of farmers.